1991
DOI: 10.1016/0140-1971(91)90006-d
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between general disease prevention and prevention of HIV‐contagion among adolescents

Abstract: A representative group of young persons (N=745), who used the youth clubs in Copenhagen were asked to fill in a structured questionnaire. A large group of the young had had their sexual debut (N=367). In respect of this group we found no correlation between prevention regarding geneeral health risk factors vs. prevention against HIV contraction. It is discussed as to whether this difference can be accepted as an expression of the fact that adolescents do not consider the risk of AIDS as something that can affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Risky HIV/AIDS-related behaviours are found to be intercorrelated (those who do not use condoms also change partners frequently), but the associations with other, non-sexual risk-related behaviours are not necessarily high (e.g. Segest et al, 1991).…”
Section: Demographic Variablesmentioning
confidence: 99%
“…Risky HIV/AIDS-related behaviours are found to be intercorrelated (those who do not use condoms also change partners frequently), but the associations with other, non-sexual risk-related behaviours are not necessarily high (e.g. Segest et al, 1991).…”
Section: Demographic Variablesmentioning
confidence: 99%
“…Rotheram-Borus and studied a group of adolescents and found that, although the youth had general knowledge about HIV risks, the knowledge did not influence their reported sexual risk behaviors. Other studies have also reflected this same lack of influence on sexual behavior, whether the knowledge involved HIV transmission (Berger & Levin, 1993;Keller et al, 1991;Segest, Mygind, Harris, & Bay, 1991) or was general knowledge about HIV and sexually transmitted diseases (STDs; Donnmeyer, Marquard, Gibson, & Taylor, 1989;Edgar, Freimuth, & Hammond, 1988;Geringer, Marks, Allen, & Armstrong, 1993;Linden, Kegeles, Hearst, Grant, & Johnson, 1990;Stevens-Smith & Remley, 1994;Winkelstein, Wiley, & radian, 1988).…”
Section: * * *mentioning
confidence: 99%
“…Of the general population of teens, 50% to 70% report sexual activity by the age of 19 (Stevens-Smith & Remley, 1994). When it comes to HIV and STDs, Segest et al (1991) found that, because of their incorrectly perceived invincibility, many teens continue to believe that they are not at risk for HIV and that AIDS may not affect them in general.…”
Section: * * *mentioning
confidence: 99%